PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 20 BABUSSALAM DURI KECAMATAN MANDAU - Reni Haryati; Lazim N '; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Results of learning achieved by students for social studies in elementary school 20 Babussalam Saber Duri Bengkalis District of class IV, has not showed the maximum results can be concluded or class IV student learning outcomes in social studies is still low. Based on the experience of researchers lower student learning outcomes in social studies is caused by: 1. In the learning of students tend to get hung up on the teacher's explanations thus less interaction between students. 2. Students assume a social studies lesson boring as it only contains stories and memorizing and 3. Students are more quiet and less confident to ask or opinion. The subjects of this study are all fourth grade students totaling 28 students. In addition, researchers use the type of classroom action research conducted in two cycles during 4 meetings. Each cycle is carried out through four stages, namely planning, action, observation, and reflection. The average value of the basic score of students is rising 61.79 to 76.86 at the end of the cycle I. replay at end of cycle II replicates increased again to 81.86. Mastery learning in the first cycle and increased 71.43% in Cycle II with 89.29%. Key Words: Make a Match, learning outcomes IPS